Energy-Efficient Aggressive Duty-Cycling of V-Band Power Amplifiers - Maximilian Gottfried Becker; Marco Gunia; Diego Mendez; Frank Ellinger (IEEE Access)
In addition to implementing the core functionality, a design goal for modern circuits is reduced energy consumption. When options for improving active state efficiency are eventually exhausted, the next step is to aggressively minimize the duration a circuit is active to reduce overall energy consumption. Consequently, this article presents a top-down study on efficient duty-cycling of power amplifiers (power amplifiers), spanning system-level considerations down to experimental measurements of a proposed V-band PA. A thorough analysis of the duty-cycling characteristics in a wireless transmitter reveals the significance of fast and efficient switching, particularly if minimal latency is desired and if energy consumption should scale linearly with required data rate. To be able to assess power amplifiers in that regard, the related key characteristics as well as transient RF power measurements are discussed. To enable aggressive duty-cycling at circuit level, the switching process is studied for integrated millimeter-wave (mmWave) class-E power amplifiers. Despite intrinsic switched mode operation at RF, transitions from sleep to active state are not instantaneous, but two phases are revealed: operating point switching (OPS) and large-signal rise in the load network. A kick-starter circuit for speeding up this transition is investigated. To prove these concepts, a two-stage 51 GHz 14 dBm SiGe PA capable of fast and efficient operational state switching is designed and fabricated. Its duty-cycling performance is measured in detail for both single-tone and modulated signals showing turn-on times in the nanosecond range. The results demonstrate highly efficient duty-cycling of data transmission at a cycle duration of just $\mathrm {1~μ \text {s} }$ for minimum latency. This article aims to allow system and circuit designers to better evaluate requirements for and performance of switchable mmWave power amplifiers in context of duty-cycled communications.